PENGEMBANGAN LKPD BERBASIS HOTS DAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN BERPIKIR KREATIF MATEMATIS - Renita Renita; M Rusdi; Syaiful Syaiful (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
Abstract This study aims to produce HOTS-based LKPD products and Problem Based Learning on linear program material oriented towards increasing the mathematical creative thinking skills and to determine the feasibility of HOTS-based LKPDs through the application of PBL models to linear program material to improve students' mathematical creative thinking abilities educate. Data collection was carried out by means of document analysis, conducting surveys, and quetionnaires. This research uses the ADDIE model which consists of five development steps, namely analyze, design, development, implementation and evaluation. The subjects of this study The subjects in this study were students of class XI IPA MAN 3 Jambi City and the objects in this study were HOTS-based worksheets. Based on the research results the developed LKPD produces positive responses and can be used in the learning process and can improve students' mathematical creative thinking skills, and the effectiveness is obtained based on the product developed which can improve students' mathematical creative thinking abilities from the results of the pre-test and post-test through the N-gain test obtained a score of 0.62, namely in the medium category and the HOTS-Based LKPD and Problem Based Learning that was developed was effective.